Qualitative comparison of polyethylene terephthalate flakes from various collection systems in Germany. Issue 2 (February 2017) - Snell, H; Nassour, A; Nelles, M
In 2003, a deposit system for one-way packaging was introduced in Germany. Since that time, polyethylene terephthalate beverage packaging is collected through various collection systems, a deposit system, a reusable packaging system and the 'Green Dot' (the dual system) with the yellow bag. The manner of collection had a decisive influence on the quality of the generated recycled materials. The research at hand shows for the first time how the quality of polyethylene terephthalate flakes depends on the type of collection system. The results are based on a 14-year time frame, during which the quality of the polyethylene terephthalate flakes was examined using the different collection systems. The criterion used was the amount of contamination of polyethylene terephthalate flakes with various polymers, metals and other substances. Grain size and bulk density were also compared. The outcome shows that material from the deposit systems resulted in a better quality of polyethylene terephthalate (PET) flakes.